Effect of Islamic fasting on the obesity factors in male and female obese subjects - Khattak, Muhammad Muzaffar Ali Khan; Abu Bakar, Ibrahim; Yeim, Liyana (Submitted to IIUM RMC, 2011)
Fasting is performed in different communities with different believes and for the management of body weight but in Islam the Muslim observes fasting in the Holy Month of Ramadan as an obligation. Therefore, this study was designed to know the effect of fasting on the obesity factors for example body weight, serum adiponectin, serum lipids and body composition assesses by bioelectrical impedance analysis (BIA). Twenty five volunteers (male & female) from the international Islamic University Malaysia (IIUM) were recruited in Ramadan. Age sex, weight, height and menstrual cycle status (in case of females) were recorded on day1 of the Ramadan and body weight was also recorded on day 21. Similarly, BIA was performed on day1 and 21 for the assessment changes in body composition. Blood samples were collected on the Day1 of the Ramadan followed by another three collection of blood samples .i.e. day7, 14 & 21 respectively. The blood serum was separated and stored at -20C̊. From weight & height basal metabolic Index (BMI) was determined. The blood was analyzed for glucose, adiponectin and lipid profiles by Bayer Health Care Kits. After 21 days of Ramadan fasting body weight was significantly (P <0.001) reduced in the obese individuals. There was significant (P<0.01) reduction in waist hip ratios in obese male and female. In the present study BIA showed no significant change in the intra or extra cellular fluids, however there has been shift of water between the two compartments which seems to be a physiological phenomenon during fasting. Infact, there was strong positive correlation (r= 0.9) between the fat free mass and total body water and similarly there was strong negative association (r= -0.9) with total body water. This study indicates that Islamic fasting could be a useful tool for the management of body weight without having major shift in the body composition. There was a decreasing trend in blood glucose concentration from day 1-21 and the decrease was 10.00%. The blood triglyceride concentration significantly reduced and the reduction was 17.48 percent from day 1-21. The blood total-Cholesterol concentration also reduced from day 1-21 and the reduction was 15.93 percent. The blood LDL-Cholesterol concentration also significantly reduced from day 1-21 and the reduction was 21.67 percent. The blood HDL-Cholesterol concentration decreased in the first weak and second week but improving trend was observed on day 21 of the Ramadan. This study indicates that Islamic fasting could be a useful tool for the management of body weight and blood lipids without having major shift in the body composition.